High-performance liquid chromatography quadrupole time-of-flight mass spectrometry (HPLC-QTOFMS) analysis on the ethanol:water (80:20) extract of lawsonia inermis leaves - Muhammad Remy Othman,; Rozana Othman,; Abdul Aziz Ismail,; Hazrina Hazni,; Khadher Ahmad,; Munirah Abd Razzak,; Zulkifli Mohd Yusoff,; Khalijah Awang, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Lawsonia inermis (Henna), (Lythraceae), contains a high amount of phenolic compounds which could activate antioxidants to help reduce free radicals. In this study, the compound content found in the ethanol:water (80:20) extract of local Lawsonia inermis was determined using HPLC-QTOFMS. The 1 H-NMR results were used to determine the peak that exists for the group compounds. Chromatographic peaks were detected and integrated by the MassHunter Acquisition B.07.00 for the Agilent TOF and QTOF and MassHunter Qualitative Analysis B.07.00. The ethanol:water (80:20) extract of L. inermis have shown, predominantly, the presence of phenolic compounds (coumarins, flavonoids, naphthalene, and gallic acid) which are highly glycosylated. The presence of compounds such as apiin, lawsone, apigenin, luteolin, cosmosiin, and p-coumaric acid were also found.